2012
DOI: 10.1177/030089161209800326
|View full text |Cite
|
Sign up to set email alerts
|

LDOC1 Gene Expression in Two Patients with Head and Neck Squamous Cell Carcinomas and Parkinson's Disease

Abstract: Introduction. Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers in the world. Risk factors for this cancer include tobacco and alcohol use, ultraviolet light exposure, and viral infection. Parkinson's disease is one of the most common neurodegenerative disorders, with a prevalence of 3% in persons over the age of 65 years. Apoptosis is a programmed cell death machinery pivotal for normal development, the establishment of highly organized neuronal circuitry, and the elimination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, the same study also revealed that upregulation of LDOC1 in subcases of unmutated chronic lymphatic leukemia was associated with poor prognosis (10). Overexpression of LDOC1 mRNA has also previously been noticed in blood cells of patients with both cutaneous and head and neck squamous cell carcinomas (22,23). Since the same group also noticed elevated LDOC1 mRNA expression in blood samples of Alzheimer patients, the involvement of LDOC1 as a proapoptotic factor in neurodegenerative disease has been assumed (23).…”
Section: Discussionmentioning
confidence: 82%
“…However, the same study also revealed that upregulation of LDOC1 in subcases of unmutated chronic lymphatic leukemia was associated with poor prognosis (10). Overexpression of LDOC1 mRNA has also previously been noticed in blood cells of patients with both cutaneous and head and neck squamous cell carcinomas (22,23). Since the same group also noticed elevated LDOC1 mRNA expression in blood samples of Alzheimer patients, the involvement of LDOC1 as a proapoptotic factor in neurodegenerative disease has been assumed (23).…”
Section: Discussionmentioning
confidence: 82%
“…, in a study of expression array on to male young onset hypertension, have suggested that innate immune response and cell‐proliferation regulation may play important downstream roles in development of hypertension and specifically that LDOC1 gene plays a key role in the regulatory mechanisms related to apoptosis in hypertension. In addition, LDOC1 gene expression was increased in Down syndrome subjects and in patients with Parkinson's disease .…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction, RT and qPCR for each sample were conducted as previously reported (13). LDOC-1 gene expression level was normalized to glyceraldehyde 3-phosphate dehydrogenase gene expression level, and the target mean crossing point definition was used to indicate the mean normalized cycle threshold (13).…”
Section: Methodsmentioning
confidence: 99%
“…The leucine zipper, down-regulated in cancer 1 (LDOC-1) gene, mapping on chromosome Xq27, codes for a nuclear protein of 146 amino acids with a molecular weight of ~17 kDa, and consists of only one exon (Online Mendelian Inheritance in Man 300402) (10). Literature data (10)(11)(12)(13)(14) have indicated greater or lesser expression of LDOC-1 in a variety of tumor types. The aim of the present study was to investigate the expression of the LDOC-1 gene in LNCaP and PC3 PCa cell lines compared with normal prostate cell lines PNT1A and PNT2 by reverse transcription-quantitative polymerase chain reaction (RT-qPCR).…”
Section: Introductionmentioning
confidence: 99%